Analisa Pengaruh Suhu Pada Sulfate Reducing Bacteria (SRB) Yang Menyebabkan Korosi Internal Di Pipa Minyak Chevron Duri - Satria, Hengky Darma; Muria, Sri Rezeki; Akbar, Fajril (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Oil pipeline in PT. Chevron Pacific Indonesia has been periodically protected with scale inhibitor injection, scale remover, coating and pigging, however it was still found internal corrosion issues that caused by SRB (Sulfate Reducing Bacteria). In effort to control growth of SRB, the research was conducted to determine the correlation between temperature of crude oil to the growth of SRB population. Variations in crude oil samples from 20 production wells, which was the actual temperature directly measured in the field, then Bart Test was conducted in laboratory to measure SRB population in every day within 8 days. The results showed that SRB population was not found for crude oil sample from production well with temperature above 150°F, while with temperature under 150°F SRB population can be found in vary population. pH range of all samples was still stay in pH range for the SRB life.Key words: Bart Test, corrosion, crude oil, pipe, production well, SRB (Sulfate Reducing Bacteria).